Health and security: Why the containment of infectious diseases alone is not enough - Daniel Gulati; Maike Voss (Stiftung Wissenschaft und Politik (SWP), 2019)
The Ebola epidemic in the Democratic Republic of the Congo (DRC) highlights the urgent need to strengthen cooperation between security, health, and development actors. As the disease spreads, the World Health Organization (WHO) has declared an international health emergency. In crisis situations like these, the interdependencies between health and security are highly complex. Which population groups and which diseases are perceived as suspected health risks, and why, is a normative question for donor countries. It has political consequences above all for affected developing countries. Where health and security are common goals, it is not enough to contain infectious diseases in developing countries. Instead, resilient, well-functioning, and accessible health systems must be established. This fosters the implementation of the human right to health, creates trust in state structures, and takes into account the security interests of other states. In the United Nations (UN) Security Council, the German government could advocate for policies based on the narrative 'stability through health.'
Keywords: 320